Series of commercialization guides for Aflasafe - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The guides were co-developed by IITA, Chemonics, and Dalberg, under a multi-year project funded by the Bill & Melinda Gates Foundation and are available online.